2018
DOI: 10.1530/rep-17-0713
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroid dependence of endoplasmic reticulum stress involvement in endometrial cell apoptosis during the human endometrial cycle

Abstract: Endoplasmic reticulum (ER) stress is a common cellular stress response that enhances apoptosis to trigger cell death. However, recent studies have shown that estrogen suppresses apoptosis by inhibiting ER stress in some cell types, suggesting that ER stress-induced apoptosis is regulated by ovarian steroid hormones. In endometrial cells, ER stress may also be controlled by ovarian steroid hormones and could be involved in apoptosis induction during the menstrual cycle. To test this hypothesis, we elucidate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…It has been reported that ER stress by realgar quantum dots induces increased expression of CHOP, and further leads to EC cell apoptosis and necrosis [28]. Additionally, previous study has demonstrated that progesterone-induced ER stress may enhance EC apoptosis through overexpression of CHOP [25]. Our microarray data showed that HERPUD1 is also significantly increased with the fold change of 11.94.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been reported that ER stress by realgar quantum dots induces increased expression of CHOP, and further leads to EC cell apoptosis and necrosis [28]. Additionally, previous study has demonstrated that progesterone-induced ER stress may enhance EC apoptosis through overexpression of CHOP [25]. Our microarray data showed that HERPUD1 is also significantly increased with the fold change of 11.94.…”
Section: Discussionsupporting
confidence: 53%
“…At the beginning of ER stress, cells activate the unfolded protein response (UPR) which is mainly regulated by three ER-located sensors, including PKR-like ER kinase (PERK), inositol-requiring enzyme 1 (IRE1) and activating transcription factor 6 (ATF6). Theses sensors initiate translational attenuation to inhibit further accumulation of misfolded proteins and to increase folding machinery, and facilitate ER-associated degradation to eliminate misfolded proteins in the ER [25]. If UPR is insufficient to alleviate the stress, it then leads to cell death [24].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of E 2 reduce progesterone and inhibit endoplasmic reticulum stress in endometrial cells 157 . Increased expression of estrogen receptor (ER) isoforms has been observed in endometriotic lesions, 158,159 suggesting their contribution in regulating proliferation of the lesions.…”
Section: Potential New Pharmaceuticals and Their Target‐signaling Pathwaysmentioning
confidence: 99%
“…Another mechanism of progestin-induced apoptosis is the promotion of endoplasmic reticulum stress [ 23 ]. MPA may increase the expression of endoplasmic reticulum stress-related molecule HERPUD1 in Ishikawa cells by activating endoplasmic reticulum stress via the progestin-PRB pathway, then inducing cell apoptosis [ 24 ].…”
Section: Mechanisms Of Progestin Repairing Endometrial Pre-cancer/cancermentioning
confidence: 99%